The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.2307/3180998
|View full text |Cite
|
Sign up to set email alerts
|

Can Women's Childbearing and Contraceptive Intentions Predict Contraceptive Demand? Findings from a Longitudinal Study in Central India

Abstract: In India, use of both contraceptive and childbearing intentions predicts contraceptive demand better than use of either indicator alone, and may thus help program planners estimate future demand for contraceptive services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 0 publications
5
48
0
Order By: Relevance
“…This finding is similar to a study in India, where it was found that women would not practice any method if they still desired additional children (Roy et al, 2003). …”
Section: Discussionsupporting
confidence: 80%
“…This finding is similar to a study in India, where it was found that women would not practice any method if they still desired additional children (Roy et al, 2003). …”
Section: Discussionsupporting
confidence: 80%
“…In part, the debate arises from basic questions about the salience of fertility preferences in low-resource settings, where fertility planning and control may not represent meaningful concepts to many women or couples (Demeny 1988;van de Walle 1992). Nevertheless, indirect support for the validity and usefulness of questions about fertility preference has been provided by a series of studies that have found a high degree of correspondence between women's stated fertility preferences and subsequent contraceptive or fertility behaviour, in India (Vlassoff 1990;Roy et al 2003) and other less developed countries (Freedman et al 1975;Hermalin et al 1979;Foreit and Suh 1980;de Silva 1991;Razzaque 2000), as well as in the consistency of respondents' fertility preferences over time (Bankole and Westoff 1998). Thus, while fertility preferences may not be meaningful for some population subgroups in specific settings, there appears to be an emerging consensus that fertility goals and preferences are important for most women of reproductive age in most developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…We do acknowledge that intentions are a poor substitute for behavior, though they are predictive of subsequent adoption (Curtis and Westoff 1996; Roy et al. 2003). When the follow‐up survey data become available, we will be able to assess the predictive power of method‐specific perceptions on contraceptive use dynamics, including method‐specific uptake and method‐specific discontinuation.…”
Section: Discussionmentioning
confidence: 99%